BACTERIOLOGICAL PROFILE OF CHILDREN WITH SICKLE CELL DISEASE - SAQQAF, SYED ATHHAR; BORKAR, RAJENDRA (International Journal of Psychosocial Rehabilitation, 2020)
The study will help to find the bacteria causing infections in children and whether any preventive measures can be implemented on clinical grounds so that the outcome ro prognosis of the disease can be improved.1.To estimate the prevalence of infection in sickle cell disease.2 To determine the cause of infections in sickle cell disease and study its outcome.Patients fulfilling selection criteria will be recruited after obtaining written consent. Detailed history including age of onset, frequency and severity of crisis, frequency of admissions and transfusions, quality of follow up, quality of treatment received will be taken. Detailed examination including anthropometry will be recorded.The information will be entered in a pre-validated pre tested proforma.The investigations will be sent:Hb%,tlc, dlc, ps-cbc, Blood culture.Other Investigations will be sent as and when required.The incidence of bacteria associated with and causing Sickle cell disease and make active interventions in order to improve to prognosis of children having sickle cell disease.Often the patients of sickle cell disease are not screened for bacterial infection and it goes unnoticed. This study will help to analyze the signicance and variation in morbidity and mortality of sickle cell patients.